Jump Street Asia (M) Sdn Bhd / Muhammad Hamizi Khairul Anwar - Khairul Anwar, Muhammad Hamizi (Faculty of Business and Management, 2023)
Jump Street Asia (M) Sdn. Bhd. is not just any ordinary trampoline park in Malaysia; it's the largest and most exhilarating one out there! With an array of trampolines, fun-filled classes, and exciting activities, Jump Street Asia offers an unforgettable experience for people of all ages. What sets them apart is their commitment to creating special moments for customers, be it birthdays, school trips, or team-building events. As a marketing intern at Jump Street Asia for six months, I had an amazing time. I jumped right into the fast-paced world of marketing, where I learned the ropes and saw how imagination and words can do amazing things. As my creativity grew, I helped come up with interesting things for the park's social media outlets. But it wasn’t just about making material; I also looked into the business and learned about its complexities and how they affect marketing tactics. In this report, it will highlight the SWOT analysis of Jump Street Asia and the recommendations that can be done. The strengths of Jump Street Asia are good brand image and having a good professional personnel which makes customers become loyal and write up good reviews for this. The flaws on the other hand are having high maintenance costs and a shortage of management staff. To tackle these, Jump Street Asia must do a preventive repair program to keep costs in check, while strategic partnerships can aid in cost-effectiveness. Jump Street Asia can cater all the opportunities including advancement of Al by incorporating VR and AR technologies and participate in tourism events such as Matta Fair. Meanwhile for the threats such as negative publicity or safety concerns proactively, Jump Street Asia must be open, honest, and compassionate, reassuring customers of their unwavering commitment to safety and satisfaction.